Nature and Properties of some Deodar (Cedrus deodara) Forest Soils of Chakrata Forest Division, U.P. - Banerjee, S. P.; Badola, K. C. (Indian Forester, 1980)
Soils of the quality age-old pure forest of deodar in Kanasar Range of Chakrata Forest Division, U.P. have been studied for their morphological characteristics and physic-chemical properties. They are fine-texture slightly acidic, organic matter rich and well supplied with N, P and K and have moderate cation exchange and high water holding capacities. Careful analysis reveals some faint pedzolic features in them.